ANALISIS TINGKAT KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Anzora Anzora; Irvandi irvandi; Riki Musriandi; Irma Aryani; Rahmi Rahmi; Rini Susiani (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Mathematical communication is a very important aspect that students must have if they want to succeed in their studies, so that mathematical communication really needs to be developed among students. In mathematical communication students can express ideas by communicating their mathematical knowledge both orally and in writing in the form of algebraic explanations, pictures, digrams or other mathematical models. This research aims to describe the level of students' abilities in mathematical communication. This research is a descriptive research with a quantitative approach. The results of the study revealed that overall the number of students who had written mathematical communication skills in the very good category reached 23.4%, the good category reached 19.1%, the fairly good category reached 25.5%, the less good category reached 21.3%, the bad category reaches 10.6%, and the average value of mathematical communication skills is in the pretty good category.